2024
DOI: 10.1038/s41467-024-48341-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of modular activity in immature cortical networks

Haleigh N. Mulholland,
Matthias Kaschube,
Gordon B. Smith

Abstract: During development, cortical activity is organized into distributed modular patterns that are a precursor of the mature columnar functional architecture. Theoretically, such structured neural activity can emerge dynamically from local synaptic interactions through a recurrent network with effective local excitation with lateral inhibition (LE/LI) connectivity. Utilizing simultaneous widefield calcium imaging and optogenetics in juvenile ferret cortex prior to eye opening, we directly test several critical pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…Computational and experimental results have suggested that prior to the developmental emergence of long- range horizontal axons (Durack and Katz 1996), such long-range correlated networks can arise through purely local interactions. Models in the form of local excitation / lateral inhibition (LELI) can account for both the presence of modular functional activity as well as millimeter-scale correlations (Smith et al 2018), and are consistent with the ability of the early cortex to self-organize unstructured inputs (Mulholland, Kaschube, and Smith 2024).…”
Section: Introductionmentioning
confidence: 79%
“…Computational and experimental results have suggested that prior to the developmental emergence of long- range horizontal axons (Durack and Katz 1996), such long-range correlated networks can arise through purely local interactions. Models in the form of local excitation / lateral inhibition (LELI) can account for both the presence of modular functional activity as well as millimeter-scale correlations (Smith et al 2018), and are consistent with the ability of the early cortex to self-organize unstructured inputs (Mulholland, Kaschube, and Smith 2024).…”
Section: Introductionmentioning
confidence: 79%